“I’ve Seen More Dead People than I thought I Would”: Vicarious Trauma Exposure among Police Support Personnel - Huey, Laura (Criminal justice and behavior, 2023)
Civilian administrative assistants who work for the Royal Canadian Mounted Police, known as Detachment Services Assistants (DSAs), are frequently exposed to materials and/or experiences that are potentially psychologically traumatic. Drawing from 49 semi-structured interviews with DSAs, we analyze how these civilian personnel experience exposure to potentially psychologically traumatic events, most notably, vicarious trauma. Specifically, we overview the types of exposure to potentially psychologically traumatic events and materials experienced by DSAs, including the impact of incidents involving children, and the occupational duties through which these exposures occur; we unpack the nuances and variability in DSAs’ occupational work, which informs such exposures; and we draw from DSAs’ experiences to offer recommendations for ameliorating the mental health toll of civilian police work. The study adds to the limited academic literature on the occupational and mental health experiences of civilian personnel, who serve a vital, but underrecognized, role in supporting police operations.